Performance of Rice Grain Conveyor Vacuum Blower with Variations in the Number and Shape of Impeller Angles - Suwandi, Dedi; Sifa, Agus; Endramawan, Tito; Sumeru, Kasni (Universitas Negeri Malang, 2025)
Separating rice and bran, moving rice to storage, and other processes related to moving grain or rice. In the modern rice milling industry, the process of transferring grain material already uses a pneumatic conveying system; a vacuum blower system for transferring grain is needed when milling grain to become rice. The research method used to obtain the shape of a vacuum blower with strong inlet suction power and outlet thrust is carried out by Computational Fluid Dynamics simulation and testing several types and variations in the number of blades. Simulation of forward curved blade type impellers, backward curved blade, and straight radial blade with variations in the number of 8, 10, and 12 blades. From the impeller simulation, it was obtained that the straight radial blade with 8 blades was the best. The best impeller types were made using the manual method. Measurement results were on the straight radial blade type impeller with 8 blades, with a motor speed of 1,000 rpm; the results of measuring air speed at the inlet were 34.95 m/s and at the outlet 23.08 m/s. In addition, the difference in the results between in simulation and the experiment is due to the fabrication process and air leaks.